2020
DOI: 10.4085/1062-6050-75-18
|View full text |Cite
|
Sign up to set email alerts
|

Functional Performance of Firefighters After Exposure to Environmental Conditions and Exercise

Abstract: Context Slips, trips, and falls are leading causes of musculoskeletal injuries in firefighters. Researchers have hypothesized that heat stress is the major contributing factor to these fireground injuries. Objective To examine the effect of environmental conditions, including hot and ambient temperatures, and exercise on functional and physiological outcome measures, including balance, rectal temperature, and perceived exerti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…There were only a few intervention studies identified and all of them involved FFs. A study of balance in FFs found that the combined effect of physical effort and heat stress led to an increased likelihood of slips, trips, and falls on the fireground 58 . A prospective study found a sleep health program resulted in significantly fewer reported injuries among FFs 110 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were only a few intervention studies identified and all of them involved FFs. A study of balance in FFs found that the combined effect of physical effort and heat stress led to an increased likelihood of slips, trips, and falls on the fireground 58 . A prospective study found a sleep health program resulted in significantly fewer reported injuries among FFs 110 .…”
Section: Resultsmentioning
confidence: 99%
“…A study of balance in FFs found that the combined effect of physical effort and heat stress led to an increased likelihood of slips, trips, and falls on the fireground. 58 A prospective study found a sleep health program resulted in significantly fewer reported injuries among FFs. 110 A proactive risk management program intervention among FFs reduced injuries, and workers' compensation claims and costs, but did not result in significant changes in injury rates.…”
Section: Injurymentioning
confidence: 99%
“…6 Heat stress is not only a hazard to the cardiovascular system, but can play a role in muscle fatigue and overexertion. 20,21 Physiological and thermoregulatory strain induced by overexertion during firefighting work can also lead to performance decrements and musculoskeletal injuries. Combining the effects of exercise and heat impairs firefighter-specific functional balance and increases the likelihood of slips, trips, and falls, which lead to musculoskeletal injuries.…”
Section: Role Of Environmental Heat Exposure and Strenuous Work In Fi...mentioning
confidence: 99%
“…Several studies have shown that the physiological, biomechanical, and occupational demands of firefighting, along with extreme environmental exposures, all combine to affect job performance (4,9,18,29,30,48,53,59,65,66,(68)(69)(70)81). Rhea et al (65) found that firefighter job performance was significantly correlated with muscular strength, local muscular endurance, and anaerobic endurance.…”
Section: Performancementioning
confidence: 99%